2009
DOI: 10.1002/gps.2282
|View full text |Cite
|
Sign up to set email alerts
|

The MMSE orientation for time domain is a strong predictor of subsequent cognitive decline in the elderly

Abstract: SUMMARY Background The mini-mental state exam (MMSE) has been used to address questions such as determination of appropriate cutoff scores for differentiation of individuals with intact cognitive function from patients with dementia and rate of cognitive decline. However, little is known about the relationship of performance in specific cognitive domains to subsequent overall decline. Objective To examine the specific and/or combined contribution of four MMSE domains (orientation for time, orientation for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 27 publications
1
59
1
1
Order By: Relevance
“…MMSE items that emerged as significant predictors of membership in a declining trajectory were similar to those identified in previous studies on predictors of risk for cognitive decline [20,27,31]. However, previous studies analyzed all participants with MCI as if they constituted a homogeneous group, despite ample evidence that they are not [9,10].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…MMSE items that emerged as significant predictors of membership in a declining trajectory were similar to those identified in previous studies on predictors of risk for cognitive decline [20,27,31]. However, previous studies analyzed all participants with MCI as if they constituted a homogeneous group, despite ample evidence that they are not [9,10].…”
Section: Discussionsupporting
confidence: 51%
“…Demographic variables such as older age have been associated with a greater rate of decline in MMSE score among people with MCI [26]; however, little is known about clinical predictors of change in cognitive ability. In a study of 505 elderly nursing home residents, orientation to time was found to predict subsequent decline in the total MMSE score [27]. Lower rates of decline were observed in people who scored high on delayed recall plus one of either attention or orientation to place.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive function was measured by the Mini-Mental State Examination (MMSE). (19) Health related quality of life was assessed by the EQ-5D. Negative values of EQ-5D were replaced by zero.…”
Section: Cross-sectional Survey Of Patients Living At Homementioning
confidence: 99%
“…For example, MMSE orientation to time and delayed recall domains predict rate of decline in patients with prodromal dementia (i.e., mild cognitive impairment) [27] and older adult nursing home residents [28], while MMSE visuoconstruction and orientation to place domains appear most sensitive to predicting falls in elderly patients [29]. Jefferson and colleagues associated Alzheimer’s disease with greater impairment in orientation to time and delayed recall domains, small vessel vascular disease with working memory and visuoconstruction domain deficits, and Parkinson’s disease with errors in sentence writing accuracy [30].…”
Section: Introductionmentioning
confidence: 99%